ENVIRONMENTAL LITERACY AND BEHAVIOUR OF AGRICULTURAL PRODUCERS-PILOT STUDY - Sabo, Stanislav; Tomić, Zdenko; Juriš, Peter; Kilíková, Maria; Milijašević, Dragana; Sabo, Ana (Journal of Agricultural Sciences (Belgrade), 2025)
Environmental literacy among agricultural producers is extremely important for sustainable agriculture and environmental protection. In the paper, we examined the knowledge, education and environmental and agricultural literacy in individual farmers as well as their influence on their work in agricultural practice. The study was performed in agricultural region, in Vojvodina, Serbia. We used a self-designed questionnaire. A meeting interview and personal visits to farmer's households were used for filling the questionnaire. All agricultural producers in the examined region had 8 years of formal and more than half have higher education; more than half also attended additional informal education in the field of agriculture, and had very good knowledge in pesticide toxicity and its environmental impact. However, after flushing the spraying tank, more than half of the farmers reported disposing leftover pesticide solution in the yard or in the sewer, not being aware of the environmental threat. The level of education, as well as the knowledge on environmental threat of pesticides did not significantly affect the behavior of agricultural producers. Although they have a high level of knowledge about the pesticide management, they do not always apply it adequately in everyday practice. Additional environmental education on the implementation of theoretical knowledge in everyday practice is needed.
Keywords: environmental literacy, agricultural producers, pesticide handling, implementation